Macroscopical Development of Same Organs in The Ovine Fetuses - Girgin, Aydın; Yılmaz, Sadık; Dinç, Gürsel; Soygüder, Zafer (Van Yüzüncü Yıl Üniversitesi, 1991)
This study was made to search the rate of development of the weights of same internal organs according to total weight and to see whether these organ weights can be used as criteria in the determination of fetal age in sheep. For this aim, 107 sheep fetuses were used the CR lenghthes, estimated ages, weights and the percentage of some internal organ weights to total weight were determined. The develpament rates of the weights of same organs such as lung, spleen, kidneys and heart showed smail changes during fetal life. The development rate of the liver decreased slowly until 100 days and this deerease continued faster after 100 days. The percent age of the weight of the brain to total weight decreased gradually throughout fetal life.

Bu çalışma, koyun fetuslerinin bazı ic organ ağırlıklarının total ağırlığa göre gelisim hızlarını ve bu organ ağırlıklarinin fetal yaş tayininde bir kriter olarak kullanılıp kullanılmayacağını araştırmak için yapıldi. Araştırmada 107 adet koyun fetasü kullanıldi. Fetuslerin CR uzunluklari, tahmini yaşlari, ağırlıklari, cinsiyeleri ve bazı iç organ ağırlıklari ile bunların vücut ağırlığına olan yüzde oranlari  tespit edildi. Akciğer, dalak, böbrekler ve kalp ağırlıklarinin total ağırlık karşısındaki gelişim hızlari fetal hayat süresince ufak değişiklikler gösterdi. Karaciğerin gelişim hızı da 100. güne kadar kısmen azalırken, bu azalma 100. günden doğuma kadar aha hızlı olarak devam etti. Beyin ağırlığının orani ise fetal hayat süresince tedricen azaldi.
KOYUN FETÜSLERİNDE BAZI ORGANLARIN MAKROSKOPİK GELİŞİMİ